Door-to-needle times in patients treated by on-site and off-site on-call neurologists. PRISA study - A. Gallardo-Tur; L. Carazo-Barrios; C. de la Cruz-Cosme (Neurología (English Edition), 2022)
Background: Hospital on-call neurology shifts are frequently on-site, but some on-call services may be off-site or mixed. Intravenous tissue plasminogen activator (tPA) is one of the main reperfusion treatments for acute ischaemic stroke (AIS). This study assesses door-to-needle times (DNT) when the neurologist is on-site or off-site. Methods: We performed a prospective, observational study from 2012 to 2017, including patients with AIS and treated with tPA. Data were collected on sex, age, door-to-scan time, scan-to-needle time, and DNT. The on-duty neurologist was on-site from 08:00 to 20:00, and on call but off-site from 20:00 to 8:00. Three groups were formed: on-site, off-site, and off-site with resident present. Results: Our sample included 138 patients. The mean age was 69.7 years, and 45.7% of patients were women. Ninety-six patients were admitted during the on-site shift, 25 during the off-site shift, and 17 during the off-site–resident present shift. Patients admitted during the on-site and off-site shifts presented DNTs of 59 and 72 minutes, respectively (P =  .003). DNTs were 59, 74, and 68 minutes (P =  .001), respectively, for the on-site, off-site, and off-site–resident present shifts; the difference between DNTs for on-site and off-site shifts was statistically significant. No differences were observed between DNTs according to time of day (morning, afternoon, or night), or between weekdays and weekends. Conclusion: DNT is influenced by whether the on-duty neurologist is on- or off-site at the time of code stroke activation. The presence of a neurology resident can reduce DNT. Resumen: Introducción: La guardia de Neurología es frecuentemente presencial; es decir, con el neurólogo presente en el centro hospitalario; pero en algunos centros, puede ser localizada o mixta. La Fibrinólisis Intravenosa (FIV) es uno de los principales tratamientos reperfusores en el Ictus Isquémico Agudo (IIA). El objetivo del siguiente trabajo es comparar el Tiempo Puerta-Aguja (TPA) durante la guardia presencial y la guardia localizada. Material y Métodos: Estudio prospectivo, observacional, desde el año 2012 hasta el 2017, en el que se incluyeron pacientes con IIA y FIV. Se recogieron datos como sexo, edad, hora del inicio de los síntomas, hora de llegada al hospital, hora de TAC, hora de inicio de FIV. Se consideró guardia de «Presencia» desde las 8:00 hasta las 20:00 y «Localizado» desde las 20:00 hasta las 08:00, dividido en 3 grupos: guardia «Presencial», guardia «Localizada» y guardia «Localizada con Residente». Resultados: N = 138. Edad media 69,7 años; mujeres 45,7%. Pacientes en guardia de «Presencia» 96, «Localizada» 42, de los cuales 17 con Residente. Ambos grupos presentaban características basales similares. Los TPA de los grupos «Presencia» y «Localizado» fueron 59 y 72 minutos respectivamente (p = 0,003). Los TPA de grupos «Presencia», «Localizada» y «Localizada con Residente» respectivamente 59; 74 y 68 minutos (p =  0,001), con significación entre «Presencia» y «Localizado». No se observaron diferencias entre el TPA dependiendo de la franja horaria de mañana, tarde y noche ni entre días laborales y días de fin de semana. Conclusión: La presencia o ausencia del neurólogo en el centro hospitalario en el momento del código ictus, influye en la demora de administración de tratamiento fibrinolítico. La presencia de residente de Neurología puede acelerar la realización del proceso.